Strukturalisme Linguistik Sebagai Pendekatan Tafsir Kontemporer; Kajian Kritis: strukturalisme linguistik, Ferdinand de Saussure, tafsir al-Qur’an, - Ahmad Kusairi; Hasbi Arijal; Muhammad Sultan Zakaria (Indonesian Journal of Islamization Studies, 2023)
This paper is titled "Linguistic Structuralism as a Contemporary Interpretative Approach." The research presented in this paper is conducted using a library research model and is presented in a descriptive-analytical framework. It seeks to describe the language analysis methods used by some Islamic scholars as approaches to reading the Quran. The method in question is Linguistic Structuralism, which was developed by Ferdinand de Saussure. Linguistic Structuralism, originally a study of pure language, has found its place as an analytical tool in the hands of Islamic scholars. This linguistic study attempts to uncover meanings and significances that give rise to a "new" meaning, a meaning represented by the text itself. Two scholars who explicitly apply several aspects of linguistic structuralism in their Quranic readings will be discussed: Muhammad Syahrur in "al-Kitāb wa al-Qur’ān Qirā’ah Muʻāṣirah" and Mohammed Arkoun in "Lectures du Coran."